Transcriptome Analysis Reveals Higher Levels of Mobile Element-Associated Abnormal Gene Transcripts in Temporal Lobe Epilepsy Patients - Hu, Kai; Liang, Ping (Frontiers in Genetics, 2021)
The mesial temporal lobe epilepsy (TLE) is the most common form of epilepsy, among which temporal lobe epilepsy patients with hippocampal sclerosis (TLE-HS) show worse drug treatment effects and prognosis. TLE has been shown to have a genetic component, but its genetic research has been mostly limited to coding sequences of genes with known association to epilepsy. Representing a major component of the genome, mobile elements (MEs) are believed to contribute to the genetic etiology of epilepsy despite limited research. We analyzed publicly available human RNA-seq-based transcriptome data to determine the role of mobile elements in epilepsy by performing de novo transcriptome assembly followed by identification of spliced gene transcripts containing mobile element (ME) sequences (ME-transcripts) to compare their frequency across different sample groups. Significantly higher levels of ME-transcripts in hippocampal tissues of epileptic patients, particularly in TLE-HS were observed. Among ME classes, SINEs were shown to be the most frequent contributor to ME-transcripts followed by LINEs and DNA transposons. These ME sequences almost in all cases represent older MEs normally located in the intron sequences. For protein coding genes, ME sequences were mostly found in the 3’-UTR regions, with a significant portion also in the coding sequences (CDS) leading to reading frame disruption. Genes associated with ME-transcripts showed enrichment for mRNA splicing process and an apparent bias in epileptic transcriptomes towards neural and epilepsy-associated genes. The findings of this study suggest that abnormal splicing involving MEs, leading to loss of function in critical genes, plays a role in epilepsy, particularly in TLE-HS, thus providing a novel insight on the molecular mechanisms underlying epileptogenesis.